Evidence-based uncertainty: do implant-related properties of titanium reduce the susceptibility to perioperative infections in clinical fracture management? A systematic review - Tanner, Michael Christopher; Fischer, Christian; Schmidmaier, Gerhard; Haubruck, Patrick (Infection, 2021)
Background  Implant-associated infections (IAI) remain a challenging complication in osteosynthesis. There is no consensus or clear evidence whether titanium offers a relevant clinical benefit over stainless steel. - Purpose  In this systematic review, we sought to determine whether the implant properties of titanium reduce the susceptibility to IAI compared to stainless steel in fracture management. - Methods  A systematic literature search in German and English was performed using specific search terms and limits. Studies published between 1995 and 1st June 2020 in the Cochrane library, MEDLINE and Web of Science databases were included. Only clinical studies comparing titanium and stainless steel implants regarding the susceptibility to infections were selected for detailed review. - Results  Five studies out of 384 papers were identified and reviewed. From the studies meeting inclusion criteria one study was a systematic review, two studies were randomized controlled studies (RCT) and two studies were of retrospective comparative nature of level IV evidence. - Conclusion  Our results show that currently, no proven advantage for titanium implants in respect to IAI can be seen in contemporary literature. Implants preserving periosteal blood-flow and minimising soft-tissue trauma show statistically significant benefits in reducing the incidence of IAI. Clinical studies providing reliable evidence regarding the influence of titanium implants on IAI and investigating the susceptibility of titanium to infection are necessary